(3JRjjf bdGFO GdYbjGf HaQGFO GdJHjGfs - (3eMeO Hf bGSe Hf eMeO Hf YHO GdhGMO GdaGSj, CHh YHO Gddg, GHf RGchQ , J (B1120 (3g` s; (3GdaJM Hf eMeO Hf YHjO Gddg Hf NGbGf GHf YHO Gddg GdbjSj, CHh fU,J (B528 (3g` s ((3CMeO Hf CHj YHO Gddg eMeO Hf bGSe Hf eMeO GHf RGchQ GdaGSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi SbGfG ef GdHjGf YddkG HYO fgd hHYO , agPG eG OYJ Edjg VQhQI bdGjO GdYbjGf , ef JaSjQ hJHjGf EQJTGa eYGfjg , ai KZhQ eHGfjg , Ydi WQjbI GdeMbbjf ai GdCYjGf s
(3BNQgG (B:s
(3hGdCUd jhSaQ , aMPaJ GdhGh GdSGcfI dhbhYgG Hjf jGA hcSQI , hCeQ GdePcQ haQ , hGdeDfK hGddg CYde , SHMGfg GfJgi eG cfG YdbfGg ai ZGHQ GdCReGf Ydi bdGFO GdYbjGf hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3ai GdeYgO fSN CNQi HQbe (B1499 (3, (B1500 (3, (B1501 (3JGQjN hGdKGfjI efgG fGbUI JUhjQkG hdeG hLOJgG cGedI agQSJgG gfG s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJGQjNs